Analisis Telaah Konsep dan Implemetasi Pendidikan Agama Islam dalam Kurikulum Merdeka di SMA An- Nurmaniyah: Dampak Implementasi Kurikulum Merdeka terhadap Pengembangan Karakter dan Nilai Keislaman Siswa - Rahmanto, Muhammad Arifin; Pakpahan, Lulu; Afifah, Khoirunnisa Luthfi; Zahra, Siti Fatimatuz; Febryanti, Khoirunnisa (IAIN Ambon, 2025)
Islamic religious education is a learning process that aims to apply or realize Islamic teachings and values in everyday life. This is in line with research that shows that Islamic religious education is a conscious effort made by educators to foster and guide students in schools so that after completing their education they are able to understand, appreciate, and practice Islamic teachings. The research method used with descriptive qu alitative methods through field research and data collection techniques consisting of observation, interviews and documentation and through triangulation analysis. The results showed that the Islamic Religious Education Curriculum at An-Nurmaniyah Tangerang High School has a significant impact on character development and understanding of students' Islamic values. With a more flexible approach, this curriculum allows students to be actively involved in the learning process which can strengthen students' faith and morals. Religious education plays an important role in Indonesia's educational landscape. This type of education focuses on character development, especially the cultivation of Akhlakul Karimah (noble character) in students, which is an important foundation for the development of moral and personal integrity. However, faith-based education not only contributes to students' character building, but also encourages the development of positive traits and performance in teachers,which in turn contributes to increased satisfaction with teachers' teaching effectiveness